2011
DOI: 10.1002/j.2055-2335.2011.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptic Ulcer Disease in Older People

Abstract: Peptic ulcer disease is a common disorder that affects millions of people worldwide. Peptic ulcer disease has a major impact on quality of life and on the utilisation of the health system when complications occur. Understanding the causative roles of Helicobacter pylori and non‐steroidal anti‐inflammatory drugs has led to changes in management of the disease. Comorbidities in older people add further complexity to treatment. This article summarises the clinical aspects of peptic ulcer disease and outlines prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
(46 reference statements)
0
10
0
1
Order By: Relevance
“…This latter finding could be explained by different daily activities of younger prisoners compared with older prisoners: Younger prisoners' lives are generally marked by more (sports) injuries that can lead to osteoarticular pain. Regarding NSAIDs, with increasing age, the human body's metabolism makes it more likely that the prescription of such medication could be contraindicated (eg, increased risk of peptic ulcer bleeding) …”
Section: Discussionmentioning
confidence: 99%
“…This latter finding could be explained by different daily activities of younger prisoners compared with older prisoners: Younger prisoners' lives are generally marked by more (sports) injuries that can lead to osteoarticular pain. Regarding NSAIDs, with increasing age, the human body's metabolism makes it more likely that the prescription of such medication could be contraindicated (eg, increased risk of peptic ulcer bleeding) …”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations for the predisposition of complicated PUD in elderly people might be that H pylori infections, poor mucosal resistance to acids, NSAID usage, and smoking are highly prevalent in elderly people. 13 15 Except for H pylori infection, which increases the risk of peptic ulcer bleeding rather than perforation, all the other aforementioned factors are associated with increased risks of peptic ulcer hemorrhage and perforation. The prevalence of H pylori infection, NSAID usage, and smoking was higher in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the literature, our findings revealed that SGBIIA, which might be indicative of the presence of complicated PUD, was performed mostly in male patients and those older than 65 years. The most common reasons for the propensity of older adults to incur complicated PUD may include a greater prevalence in the HP infection rate and the associated poor mucosal resistance for older patients, a linear increase in non-steroidal anti-inflammatory drug (NSAID) usage with age, and a greater prevalence of smoking habits in the older population [2124]. With the exception of an HP infection, unrelated to the risk of perforation, all the mentioned risk factors are associated with the risks of hemorrhage and perforation in patients with PUD.…”
Section: Discussionmentioning
confidence: 99%